1990
DOI: 10.3382/ps.0691659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Four Levels of Added Fat on Broiler Breeder Performance

Abstract: Broiler breeders were fed corn-soybean diets and reared under 8 h of incandescent light. Birds were photostimulated with a mixture of incandescent light and daylight at 20 wk of age. Corn-soybean breeder diets with 0, 2, 4, and 6% added poultry fat were fed from 24 to 64 wk of age. Daily feed allocations were adjusted to provide comparable calculated protein intake at peak egg production; calculated ME intake was 413, 437, 461, and 484 kcal per bird per day for the 0, 2, 4, and 6% added fat diets, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…The lack of an effect of dietary energy allotment on fertility and hatchability, expressed either on the basis of all eggs set or of fertile eggs, is in agreement in part with the results of Brake (1990), who showed that increasing energy allotment had no influence on hatchability. However, he showed an improvement in fertility by addition of 4% fat to the diet.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The lack of an effect of dietary energy allotment on fertility and hatchability, expressed either on the basis of all eggs set or of fertile eggs, is in agreement in part with the results of Brake (1990), who showed that increasing energy allotment had no influence on hatchability. However, he showed an improvement in fertility by addition of 4% fat to the diet.…”
Section: Discussionsupporting
confidence: 88%
“…They noted, however, that egg specific gravity was improved when hens were fed 16 or 24% less than the standard feeding regimen. In contrast to current findings, McDaniel et al (1981) and Brake (1990) found that increasing feed and energy intakes had negative influences on eggshell quality. Our results did not support their findings and indicated that dietary energy allotment had no influence on EW, SW, PS, or SWUSA.…”
Section: Discussioncontrasting
confidence: 83%
“…In this regard, fatty acids and especially linoleic acid (Brake 1990) and palmitic acid rather than oleic acid (Atteh and Leeson 1985) were observed to decrease eggshell quality, and this was attributed to formation of insoluble mineral soaps. However, Peebles et al (2000) revealed that shell quality of broiler breeder eggs was not affected by dietary fat type and level, while poultry fat increased shell quality compared to corn oil.…”
Section: Discussionmentioning
confidence: 92%
“…Fat supplementation of diets is recognized as a valuable and efficient method to meet the high-energy requirements of rapidly growing broilers and high egg-producing hens [2][3][4]. The addition of 2, 4, and 6 % poultry fat to broiler breeder diets, without increasing metabolizable energy intake, has been reported to improve egg production and feed conversion efficiency [5].…”
Section: Introductionmentioning
confidence: 99%